Hollow MXene Sphere/Reduced Graphene Aerogel Composites for Piezoresistive Sensor with Ultra‐High Sensitivity. (18th December 2019) - Zhu, Meng; Yue, Yang; Cheng, Yongfa; Zhang, Yanan; Su, Jun; Long, Fei; Jiang, Xueliang; Ma, Yanan; Gao, Yihua
Abstract: Pressure sensing is key to smart wearable electronics and human–machine interaction interfaces. To achieve a high‐performance pressure sensor that has broad linear range and is capable of detecting subtle changes of pressure, the good choice of sensing materials and rational design of structures are both needed. A novel piezoresistive sensor based on hollow MXene spheres/reduced graphene composite aerogel and flexible interdigital electrodes is presented. Benefiting from the unique microstructure of the composite aerogel, the prepared pressure sensor exhibits high sensitivity (609 kPa −1 in the range of 6.4–10 kPa), broad linear range (0–10 kPa), low detection limit (6 Pa), short response time (232 ms), and good durability (6000 cycles). Moreover, the device is able to monitor various human activities in real time, as well as distinguish tiny differences of grain. The potential application of mapping the location and intensity of the pressures is also explored. Abstract : A piezoresistive pressure sensor fabricated from hollow MXene‐sphere/reduced graphene oxide composite aerogel and flexible interdigital electrodes exhibits ultra‐high sensitivity in broad linear pressure ranges. The introduction of hollow MXene spheres greatly enhances the sensing performance of the pressure sensor, making the device capable of detecting subtle pressures. The device also demonstrates promising applications in monitoring human activities in real time.